Corporate Social Responsibility and International Business: A Study of the Impact on Firm Performance - Christine Cicilia Saputra; Rivaldo Martadinata Anthonie; Hwihanus Hwihanus (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Corporate Social Responsibility (CSR) has evolved from a philanthropic initiative to an important strategic component of global business operations. CSR is now seen as an element that influences a company's image, financial performance, and stakeholder relationships. Effective CSR implementation can provide a range of benefits to international companies, including enhanced reputation, customer loyalty, and operational efficiency. This article explores the impact of CSR on firm performance by analyzing case studies from five countries: Turkey, Nigeria, China, Bangladesh, and Spain. The research method used is a qualitative meta-analysis to identify common patterns and findings from various studies. The results show that CSR implementation has a significant impact on firm performance, although it varies depending on the geographical and industry context. This article highlights the importance of a systematic approach in integrating CSR to achieve optimal results for companies.